On the relationship between analyst reports and corporate disclosures: Exploring the roles of information discovery and interpretation - Chen, Xia; Cheng, Qiang; Lo, Kin (Journal of Accounting and Economics, 2010)
We examine the relationship between analyst research and corporate earnings announcements to explore the relative importance of information discovery versus interpretation of previously released information. Using equity market reaction to capture information content, we find that information discovery (interpretation) dominates in the week before (after) firms announce their earnings. In addition, we find that the interpretation role increases in importance with the difficulty of financial accounting information. Analysis of all weeks surrounding earnings announcements shows that the information discovery role is overall more important. We are able to reconcile this result with the opposite finding in Francis et al. (2002).